Cultural and Social Mediation of Emotions (on Materials of Cross-Cultural Studies) - Ivanova, Tetyana (Visnyk of V. N. Karazin Kharkiv National University. Series Sociological studies of contemporary society: methodology, theory, methods, 2019)
Approaches to understanding the positive and negative emotions are analyzed. It is shown that Western culture is characterized by contrasting positive and negative emotions, for the culture of the East - the understanding of the interaction. Emotional characteristics are analyzed within the classification of such characteristics - individualism/collectivism, femininity/masculinity and power distance. It is shown that the regulation and assessment of positive and negative emotions society uses a variety of mechanisms. These mechanisms are, on the one hand, a subjective measurement, on the other - are developed within the framework of the cultural script and cultural context.